PROTECTION OF WOMEN'S RIGHTS IN DETERMINING REPRODUCTIVE HEALTH RELATED TO FAMILY PLANNING POLICY BY THE GOVERNMENT - Anom Saputra, Ign Agung Wira; Yustianno, Tiar (Universitas Ekasakti, 2023)
Problems in the policy aspect of the family planning program, although it is a concrete form of increasing awareness and community participation through maturing the age of marriage, birth control, fostering family resilience, increasing family welfare to create happy and prosperous small families, but the program is a form of restraining women's rights. to determine and regulate reproductive aspects, because the reproductive health aspect of women is a basic right that must be given fulfillment of needs without any discriminatory actions or policies. The existence of this program seems to be a program that must be followed by all women of childbearing age by using Family Planning officers to attract women without any process, so that these women are limited in terms of reproductive affairs, and women do not have the right to their reproductive organs. determine what program is suitable for him, when and how many will have children. The government is obliged to review the existence of this policy so that there are no restrictions on rights in terms of determining the reproductive aspects of women.